MOLECULAR IDENTIFICATION OF VENERIDE CLAM Meretris casta USING NUCLEAR RIBOSOMAL DNA, FROM SOUTHERN KERALA, INDIA - AMPILI, M.; SHINY, S. K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
The study was aimed to amplify, sequence and analyse the ITS in the nuclear ribosomal DNA of Venerid clam Meretrix casta. Adinine-Thymine (AT) content, Guanine-Cytosine (GC) content of the sequences were analysed. ITS1 region rendered three dinucleotide microsatellites, ITS2 region depicted two dinucleotide microsatellites. The sequence (NCBI GenBank Accession No. KC416613) also illustrated conserved motifs in the ITS1 and ITS2 regions. ITS1 displayed two conserved motifs respectively with 30 base pairs (bp) and 25bp. The ITS2 depicted two conserved motifs with 20bp and 21 bp. Conserved motifs exhibited transversion and/or transition polymorphic sites. ITSs are species dependent and the differences could be significant among species. The dinucleotide microsatellites contained in ITS sequence can be used as good markers. Internal transcribed Spacers (ITS) of nuclear ribosomal DNA were found to be suitable for species identification and in their molecular phylogenetic studies. Since ITS sequce of rDNA allow comparison among related species, it constitutes a good species-specific molecular marker. Furthermore ribosomal genes allow correct identification and traceability of sea food products including molluscs, thus preventing incorrect labelling when these products are offered for sale as processed food.